1980
DOI: 10.1159/000207381
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte and Plasma Lipids in Terminal Renal Insufficiency

Abstract: Lipids in erythrocytes and plasma of children and adults with terminal renal insufficiency were determined and compared with those of normal controls. The erythrocyte phospholipids in uremic patients were altered in phosphatidylethanolamine (absolutely and relatively elevated) and in lecithin (relatively diminished). Sphingomyelin, phosphatidylserine, total erythrocyte phospholipid content and cholesterol were within the normal range. The detailed analysis of the distribution of plasma phospholipids showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In fact, cells from uremic patients show a decrease in the parameter which mea sures a transport of Na+ with the properties of a nonspe cific 'leak' across the lipid bilayer of the cell membrane [7]. Changes in the lipid composition and distribution of the red blood cell membrane, as those previously re ported in uremic patients [8,9], might be involved in the observed alteration in passive Na+ fluxes. In addition, this alteration may be partially responsible for the low Na+ concentration found in erythrocytes from hemodi alysis patients.…”
mentioning
confidence: 69%
“…In fact, cells from uremic patients show a decrease in the parameter which mea sures a transport of Na+ with the properties of a nonspe cific 'leak' across the lipid bilayer of the cell membrane [7]. Changes in the lipid composition and distribution of the red blood cell membrane, as those previously re ported in uremic patients [8,9], might be involved in the observed alteration in passive Na+ fluxes. In addition, this alteration may be partially responsible for the low Na+ concentration found in erythrocytes from hemodi alysis patients.…”
mentioning
confidence: 69%
“…Patients with uremia have been found to have not only a decrease in LCAT activity, 40 but also an increased activity of phospholipase A 2 . 41 Conflicting results have been obtained from studies analysing the differences in phospholipid concentrations in blood plasma of patients with renal insufficiency, chronic renal failure and uremia (when compared with healthy volunteers): Bleiber et al 42 found an increase in all phospholipids except phosphatidylserine, Gillet et al 40 found a decrease of LPC, Vecino et al 41 found similar levels of LPC but an increase of PC, whereas Kalofoutis et al 43 found an increase for sphingomyelin, phosphatidylethanolamine and cardiolipin, but a decrease for phosphatidylinositol. In patients with nephrotic syndrome variations in plasma LCAT activity could also be found.…”
Section: -26mentioning
confidence: 99%
“…In contrast to findings from Quarello et al 16 ) , the authors have found that the passive Na + permeability in the patients with pre-dialytic uremia was markedly decreased compared to that in normal subjects (p<10 −5 ), but its value in the post-dialytic group tended to recover to a normal level, which was consistent with a previous report by Diez et al 18 ) . Although the exact mechamism for inhibition of passive Na + permeability in chronic uremia is as yet uncertain, changes in the lipid composition and distribution of the RBC membranes, as Bleiber et al previously reported in uremic patients, might be involved in the observed alteration in passive Na + fluxes 34 ) .…”
Section: Discussionmentioning
confidence: 96%